TRANSFORMING GRADUATE STUDIES THROUGH DECOLONIZATION: SHARING THE LEARNING JOURNEY OF A SPECIALIZED COHORT - Kearns, Laura-Lee; Tompkins, Joanne; Lunney Borden, Lisa (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2018)
This study traces the learning journey of primarily non-Indigenous educators who challenged the legacy of colonization in schools, and worked to decolonize their practice, through their participation in a specialized graduate cohort. Drawing upon sharing circle conversations, we highlight themes that emerged from our research. Educators reported their sense of agency to transform and change their practice increased with the support of a critical and caring learning community. In nourishing their learning spirits, educators were able to begin to decolonize education, an ongoing challenge that requires valuing Indigenous people, languages, and land, and building inter-cultural understanding. This study is an example of how graduate programming can begin to address the Calls to Action of the Truth and Reconciliation Commission.